Propriedades estruturais e vibracionais de nanocristais de TiO2 dispersos em matriz vítrea porosa - Viana Neto, Bartolomeu Cruz (2006)
Nanostructured materials are the subject of intense investigation due to their remarkable properties as compared their bulk counterparts. The size-induced phenomena are interesting their own and open unique opportunities not only for using these properties in novel applications but also for improving the current technology. In this scenario integrated chemical systems (ICS) are set apart owing their complexity and the possibility ofcombining diferent nanosystems for getting materials with a designed functionality. For instance, nanocrystal growth in the cavities of a porous host is an attractive ICS because the porous is a restricted environment that can be used as nanoreactors. Besides the such system is very promising for catalysis it also important for studying the size-induced properties of the guest material as well. In this work we report the study of vibrational and structural properties of TiO2 nanocrystals dispersed into a porous vycor glass. We have obtained very small TiO2 nanocrystals in the anatase form. The nanocrystal size is controlled via the mass increment only thus preventing the growth through the coalescence process. The nanocrystal size as monitored through transmission electron microscope and Raman scattering. The Eg lowest frequency mode experiences an upshift and becomes broader as the nanocrystal size decreases. This phenomena is attributed to a size-induced e®ect and we analyzed it based on a phonon con¯nement model. As the nanocrystal size gets smaller the q = 0 selection rule is relaxed and the phonon con¯nement involves large q values contribute to the Raman intensity. The frequency follows the same trend of the phonon dispersion relation for the TiO2 bulk as the nanocrystal size decreases.